Improving polynomial datapath debugging with HEDs - Sadeghi-Kohan, Somayeh; Behnam, Payman; Alizadeh, Bijan; Fujita, Masahiro; Navabi, Zainalabedin (2014 19th IEEE European Test Symposium (ETS))

Influence of aluminium on the corrosion behaviour of binary magnesium-aluminium alloys in saline solutions - Hoyer, Kay-Peter; Angrisani, Gian Luigi; Klose, Christian; Bach, Friedrich-Wilhelm; Hassel, Thomas (Materials and Corrosion)

Ontology Based Data Access and Integration for Improving the Effectiveness of Farming in Nepal - Pokharel, Suresh; Sherif, Mohamed; Lehmann, Jens (Proc. of the International Conference on Web Intelligence)
It is widely accepted that food supply and quality are major problems in the 21st century. Due to the growth of the world's population, there is a pressing need to improve the productivity of agricultural crops, which hinges on different factors such as geographical location, soil type, weather condition and particular attributes of the crops to plant. In many regions of the world, information about those factors is not readily accessible and dispersed across a multitude of different sources. One of those regions is Nepal, in which the lack of access to this knowledge poses a significant burden for agricultural planning and decision making. Making such knowledge more accessible can boot up a farmer's living standard and increase their competitiveness on national and global markets. In this article, we show how we converted several available, although not easily accessible, datasets to RDF, thereby lowering the barrier for data re-usage and integration. We describe the conversion, linking, and publication process as well as use cases, which can be implemented using the farming datasets in Nepal.
Keywords: group_aksw MOLE 2014 sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:geoknow topic_geospatial lehmann sherif simba dice

NIF4OGGD - NLP Interchange Format for Open German Governmental Data - Sherif, Mohamed; Coelho, Sandro; Usbeck, Ricardo; Hellmann, Sebastian; Lehmann, Jens; Brümmer, Martin; Both, Andreas (The 9th edition of the Language Resources and Evaluation Conference, 26-31 May, Reykjavik, Iceland)
In the last couple of years the amount of structured open government data has increased significantly. Already now, citizens are able to leverage the advantages of open data through increased transparency and better opportunities to take part in governmental decision making processes. Our approach increases the interoperability of existing but distributed open governmental datasets by converting them to the RDF-based NLP Interchange Format (NIF). Furthermore, we integrate the converted data into a geodata store and present a user interface for querying this data via a keyword-based search. The language resource generated in this project is publicly available for download and via a dedicated SPARQL endpoint.
Keywords: 2014 dice simba sherif sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:geoknow hellmann kilt lehmann usbeck bruemmer nif4oggd group_aksw kilt Lidmole MOLE

Unsupervised Link Discovery Through Knowledge Base Repair - Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed; Lyko, Klaus (Extended Semantic Web Conference (ESWC 2014))
The Linked Data Web has developed into a compendium of partly very large datasets. Devising efficient approaches to compute links between these datasets is thus central to achieve the vision behind the Data Web. Several unsupervised approaches have been developed to achieve this goal. Yet, so far, none of these approaches makes use of the replication of resources across several knowledge bases to improve the accuracy it achieves while linking. In this paper, we present Colibri, an iterative unsupervised approach for link discovery. Colibri allows discovering links between n datasets (n ≥ 2) while improving the quality of the instance data in these datasets. To this end, Colibri combines error detection and correction with unsupervised link discovery. We evaluate our approach on benchmark datasets with respect to the F-score itachieves. Our results suggest that Colibri can significantly improve the results of unsupervised machine-learning approaches for link discovery while correctly detecting erroneous resources.
Keywords: ngonga sherif lyko simba group_aksw sys:relevantFor:infai sys:relevantFor:bis SIMBA DICE limes

Semantic Quran: A Multilingual Resource for Natural-Language Processing - Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Semantic Web Journal)
In this paper we describe the Semantic Quran dataset, a multilingual RDF representation of translations of the Quran. The dataset was created by integrating data from two different semi-structured sources and aligned to an ontology designed to represent multilingual data from sources with a hierarchical structure. The resulting RDF data encompasses 43 different languages which belong to the most under-represented languages in the Linked Data Cloud, including Arabic, Amharic and Amazigh. We designed the dataset to be easily usable in natural-language processing applications with the goal of facilitating the development of knowledge extraction tools for these languages. In particular, the Semantic Quran is compatible with the Natural-Language Interchange Format and contains explicit morpho-syntactic information on the utilized terms. We present the ontology devised for structuring the data. We also provide the transformation rules implemented in our extraction framework. Finally, we detail the link creation process as well as possible usage scenarios for the Semantic Quran dataset.
Keywords: group_aksw SIMBA sys:relevantFor:infai sys:relevantFor:bis ngonga limes simba dice sherif 2014 limes semanticquran

The GeoKnow Generator: Managing Geospatial Data in the Linked Data Web - Jay Le Grange, Jon; Lehmann, Jens; Athanasiou, Spiros; Garcia Rojas, Alejandra; Giannopoulos, Giorgos; Hladky, Daniel; Isele, Robert; Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed; Stadler, Claus; Wauer, Matthias (Proceedings of the Linking Geospatial Data Workshop)
Keywords: 2014 group_aksw group_mole mole ngonga lehmann sherif topic_Lifecycle sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:lod2 sys:relevantFor:geoknow geoknow lod lod2page peer-reviewed MOLE simba dice wauer stadler

The Influence of Peers and Politics on Economic Outcomes - Empirical and Experimental Evidence in the Fields of Social Norms, Politically Connected Firms, Taxation and Climate Change - Janssen, Elmar

Anhaltende Ausgrenzung. Diskriminierung und rassistische Verfolgung von ‘Zigeunern’ in Osnab-rück von den 1920er bis in die 1950er Jahre - Schubert, Michael; Cooper, Duncan (Jahresbericht 2014 der Stiftung niedersächsische Gedenkstätten)

Anhaltende Ausgrenzung. Diskriminierung und rassistische Verfolgung von ‚Zigeunern’ in Osnabrück von den 1920er bis in die 1950er Jahre - Schubert, Michael; Cooper, Duncan

(for the ActiFE study group) Multisite pain, pain frequency and pain severity are associated with depression in older adults: results from the ActiFE Ulm study - Denkinger, M.; Lukas, A.; Nikolaus, Th.; Peter, R.; Franke, Sebastian (Age and Ageing)

Berufsfeld Schulbegleitung. Eine Studie zum Einsatz von Schulbegleiter/innen an Förderschulen in NRW - Mays, D.; Franke, Sebastian; Ladinig, B.; Kißgen, R. (Schulverwaltung NRW)

Schulbegleitung an Förderschulen in Nordrhein-Westfalen: Ausgangslage, Studienkonzeption und erste Ergebnisse - Kißgen, R.; Franke, Sebastian; Ladinig, B.; Mays, D.; Carlitscheck, J. (autismus)

Service transition: A viable option for manufacturing companies with declining financial performance? - Eggert, A.; Münkhoff, Eva; Thiesbrummel, C. (43rd EMAC Annual Conference, Valencia)

Service transition versus service infusion: Different pathways to success for service-oriented manufacturers? - Kanuri, V.; Münkhoff, Eva; Scheer, L. K. (ISBM 2014 Academic Conference, San Francisco, CA)

Salespersons’ solution crafting capability: A knowledge-based perspective - Münkhoff, Eva; Eggert, A.; Terho, H.; Haas, A.; Ulaga, W. (ISBM 2014 Academic Conference, San Francisco, CA)

Selling value in business markets: Why a powerful idea often fails - Eggert, A.; Haas, A.; Terho, H.; Ulaga, W.; Münkhoff, Eva (ISBM 2014 Academic Conference, San Francisco, CA)

Ästhetisches Lebenspathos und seine parodistische Kontrafaktur. Goethes „Faust“ sowie Hofmannsthals „Der Tor und der Tod“ vs. Schnitzlers „Anatol“ - Elit, Stefan (Wirkendes Wort)

Revenue and Profit Implications of Industrial Service Strategies - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Münkhoff, Eva (Journal of Service Research)
In many business markets, manufacturers seek service-led growth to secure their existing positions and continue to grow in increasingly competitive environments. Using longitudinal data from 513 German mechanical engineering companies and latent growth curve modeling, this study offers a fine-grained view of the financial performance implications of industrial service strategies. By disentangling the revenue and profit implications of industrial service strategies, findings reveal that such strategies increase both the level and the growth of manufacturing firms’ revenue streams. In contrast, they reduce the level but improve the growth of manufacturers’ profits. Results further suggest that services supporting the clients’ actions (SSC) and services supporting the supplier’s product (SSP) affect performance outcomes in different ways. SSCs directly affect revenue and profit streams. In turn, SSPs display only indirect effects on financial performance mediated through SSCs. A moderator analysis identifies two organizational contingencies that facilitate service business success: Only companies with decentralized decision-making processes and a high share of loyal customers can expect favorable financial results from industrial service strategies. In summary, this research provides significant insights and managerial guidance for turning service strategies into financial successes.
Keywords: Organizational Behavior and Human Resource Management; Sociology and Political Science; Information Systems

Expertise affects representation structure and categorical activation of grasp postures in climbing - Bläsing, Bettina E; Güldenpenning, Iris; Koester, Dirk; Schack, Thomas (Frontiers in Psychology)